The accordion worm: a new genus and species of heteronemertean (Nemertea, Pilidiophora) from Galicia (Spain) - Aida Verdes; Carlota Gracia-Sancha; Jacinto Pérez-Dieste; María Conejero; Patricia Alvarez Campos; Carlos Leiva; Sergi Taboada; Ana Riesgo; Juan Junoy (Royal Society Open Science)
Ribbon worms (Nemertea) are a less-known group of invertebrates, specially challenging for taxonomic studies due to the scarcity of external morphological features. As a consequence, the number of known nemertean species might represent just a small fraction of the true diversity of the phylum. The present study increases the number of known ribbon worm species with the description of the accordion worm Pararosa vigarae sp. nov., a new genus and species of Heternonemertea from the northwest coast of Spain. We performed molecular phylogenetic analyses based on partial sequences of 16S rRNA, 18S rRNA, 28S rRNA, cytochrome c oxidase subunit I (COI) and histone H3 gene markers that indicated the newly identified specimens represent a new genus and species of heteronemertean in the family Lineidae. We also provide morphological data and images illustrating its unique behaviour, contracting its body into a series of rings similar to an accordion. Our results increase our knowledge on the diversity of an important but often overlooked invertebrate phylum and emphasize the need to combine morphological and molecular data to discover new ribbon worm species and better evaluate the true diversity of the phylum.